1997
DOI: 10.1002/(sici)1097-0142(19970101)79:1<152::aid-cncr22>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting cancer patients to participate in motivating their relatives to quit smoking

Abstract: The intervention proved to be feasible and will lead to the next study, which will randomize relatives who smoke within a more intensive intervention over 12 months and compare the results with nonintervention controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Besides the intervention by Schilling et al (1997), which exclusively targeted family members of recently diagnosed cancer patients who smoked, only four other studies addressed smoking among participants’ family members (Browning, Ahijevych, & Ross, 2000; Emmons et al, 2005; Sharp, Johansson, Fagerstrom, & Rutqvist, 2008; Wakefield, Olver, Whitford, & Rosenfeld, 2004). In the Wakefield and colleagues’ study, patients’ family members were made aware of the need to quit in support of the patient’s quit attempt, while Emmons and colleagues provided NRT to subjects’ partners–spouses who smoked and requested NRT.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the intervention by Schilling et al (1997), which exclusively targeted family members of recently diagnosed cancer patients who smoked, only four other studies addressed smoking among participants’ family members (Browning, Ahijevych, & Ross, 2000; Emmons et al, 2005; Sharp, Johansson, Fagerstrom, & Rutqvist, 2008; Wakefield, Olver, Whitford, & Rosenfeld, 2004). In the Wakefield and colleagues’ study, patients’ family members were made aware of the need to quit in support of the patient’s quit attempt, while Emmons and colleagues provided NRT to subjects’ partners–spouses who smoked and requested NRT.…”
Section: Resultsmentioning
confidence: 99%
“…10 However, in a study of smoking relatives of lung cancer patients, 91% of smoking family members still smoked following an educational intervention about the benefits of smoking cessation. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Research shows that cancer patients who smoke are likely to have family members who smoke (14). One cessation trial recruiting smoking relatives of cancer patients reported that on average, cancer patients have two relatives who smoke (17) and a recent study reported that 18% of family caregivers of women with lung cancer continued smoking after the diagnosis(18). …”
Section: Introductionmentioning
confidence: 99%